Enquanto os adultos brincam: Introdução aos processos próprios de ensino-aprendizagem da criança kaingang - Josué Carvalho (2016)
The thesis brings, above all, own forms of learning of the child belonging to the Kaingang People of Nonoai Indigenous Territory (RS). Their ways of socializing in the group from their daily life and in ritualistic moments, weddings, girl's rite of passage to women, the formation of a spiritual leader (Kujá) and cultural events inherent to the day of the Indian, "April 19th". These moments only happen in the hamlet in specific times and contexts. In these moments the child comes into collision with what is hers and the ways of acting, taking in the sights the other's gaze, especially when the other is not an Indian. I intend, over the thesis, to realize the child's views on the part of older, mostly parallel to other languages of conceiving a child with that, over time, the Kaingang families were being affected by the arrival of the school, religion, the surrounding culture. I also present an actual conversation with the children and from children, their desires, their conceptions about themselves. In the research I seek for a dialogue on child anthropology field, with interfaces to other different areas as education, communication, sociology and museology, but it is in the everyday child's doings, in the analysis of their own contexts of teaching, learning and socialization that the study is justified, sets up and takes shape.